STELO: a new tool for family physicians for the correct identification of inherited cancer syndromes. (19th September 2019) - Mariani, Chiara; Carnevali, Ileana; Lapi, Francesco; Paganini, Elisa; Civitelli, Chiara; Muzzolon, Jessica; Franzetti, Anna; Guerroni, Alessandro; Tibiletti, Maria Grazia
Abstract: Background: The hereditary cancer syndromes represent overall <10% of all cancers. These syndromes are not irrelevant for public health because all the cancers typical of these syndromes affected young people and many members of the same family and the cancers are more aggressive than the sporadic ones and need specific surgery and medical therapy. We developed a new family assessment tool: STELO designed for family physicians to identify patients could benefit from Cancer Genetic Counselling. Objective: Test the sensitivity and specificity of a new assessment tool for the correct identification of inherited cancer syndromes. Methods: Retrospectively we tested the new tool on a subset of patients who had already undergone genetic counselling at the Cancer Genetic Counselling Service of ASST (Azienda Socio Sanitaria Territoriale) Settelaghi Varese, to investigate sensitivity, specificity and applicability of this new tool in routine genetic screening. STELO responses were matched against the opinion of two cancer geneticists (i.e. gold standard) who blinded each other decided if the history of these patients was properly suspected as a hereditary cancer syndrome. Results: The Genetic Counselling Service followed 546 subjects from 2014 to 2015. STELO tool was tested retrospectively on these clinical records and resulted positive in 418 cases, out of 546 (76.5%). STELO reported, towards the gold standard, 88.5% and 52.3% of sensitivity and specificity, respectively. Conclusions: STELO has demonstrated to have a good sensitivity. The specificity was expectedly low given that STELO has been developed for general medicine, so it needs to be simple, practical, of rapid consultation and effectively used in clinical practice.